Fumarate hydratase c.914T > C (p.Phe305Ser) is a pathogenic variant associated with hereditary leiomyomatosis and renal cell cancer syndrome. Issue 8 (28th May 2020) - Breen, Kelsey E.; Carlo, Maria I.; Kemel, Yelena; Maio, Anna; Chen, Ying‐Bei; Zhang, Liying; Ceyhan‐Birsoy, Ozge; Mandelker, Diana
Abstract: Background: Hereditary leiomyomatosis and renal cell cancer syndrome (HLRCC), caused by heterozygous germline pathogenic variants in the FH, confers an increased risk for cutaneous and uterine leiomyomas and renal cancer. Methods: About 13, 722 advanced cancer patients, including 560 with renal cell carcinoma, had germline analysis performed in the context of tumor‐normal sequencing under an IRB approved protocol. Results: We report two unrelated individuals with early onset kidney cancer who both carried the c.914C > T (p.Phe305Ser) germline variant in the FH . Both tumors exhibited loss of FH staining by immunohistochemistry and/or positive 2SC staining. Subsequent familial testing discovered that a daughter of a proband who carried the variant had both cutaneous and uterine leiomyomas. Conclusion: This combination of evidence suggests that the FH c.914C > T (p.Phe305Ser) is pathogenic for HLRCC. Abstract : Immunohistochemical analysis of kidney tumors from two unrelated patients with the germline FH c.914T > C (p.Phe305Ser) variant revealed a loss of fumarate hydratase (FH) staining and positive S‐(2‐succino)‐cysteine (2SC) staining. We provide evidence to suggest the FH variant c.914C > T (p.Phe305Ser) is pathogenic for HLRCC.